Success rate evaluation of clinical governance implementation in teaching hospitals in Kerman (Iran) based on nine steps of Karsh’s model - Vali, Leila (Electron Physician, 2017)
BACKGROUND: One of the ways to improve the quality of services in the health system is through clinical governance. This method aims to create a framework for clinical services providers to be accountable in return for continuing improvement of quality and maintaining standards of services. OBJECTIVE: To evaluate the success rate of clinical governance implementation in Kerman teaching hospitals based on 9 steps of Karsh’s Model. METHODS: This cross-sectional study was conducted in 2015 on 94 people including chief executive officers (CEOs), nursing managers, clinical governance managers and experts, head nurses and nurses. The required data were collected through a researcher-made questionnaire containing 38 questions with three-point Likert Scale (good, moderate, and weak). The Karsh’s Model consists of nine steps including top management commitment to change, accountability for change, creating a structured approach for change, training, pilot implementation, communication, feedback, simulation, and end-user participation. Data analysis using descriptive statistics and Mann-Whitney-Wilcoxon test was done by SPSS software version 16. RESULTS: About 81.9 % of respondents were female and 74.5 have a Bachelor of Nursing (BN) degree. In general, the status of clinical governance implementation in studied hospitals based on 9 steps of the model was 44 % (moderate). A significant relationship was observed among accountability and organizational position (p=0.0012) and field of study (p=0.000). Also, there were significant relationships between structure-based approach and organizational position (p=0.007), communication and demographic characteristics (p=0.000), and end-user participation with organizational position (p=0.03). CONCLUSION: Clinical governance should be implemented by correct needs assessment and participation of all stakeholders, to ensure its enforcement in practice, and to enhance the quality of services.